The Effect of Plyometric Exercises (Jumping Lunges and Squat Jump) on Hapkido Dollyo Chagi's Kick Power Central Lampung Hapkido Athletes - Reza Jasindo Putra; Surisman; Candra Kurniawan; Fransiskus Nurseto (Universitas PGRI Palembang, 2025)
This study aims to determine the effect of plyometric training (jumping lunges and squat jumps) on the kick power of hapkido dollyo chagi Central Lampung hapkido athletes. The research method used in this research was a descriptive experiment and the samples used were 40 male Hapkido athletes (aged 16-18 years), Central Lampung, totaling 40 people. The instrument used was the dollyo chagi power test. The research results show that: 1). There is a significant influence from Jumping Lunges training on the kick power of hapkido dollyo chagi Central Lampung hapkido athletes with a percentage increase of 7.6% with a calculated t value > t table, 7.967 > 1.729 which means it is very influential. 2). There is a significant influence from Squat Jump training on the kick power of hapkido dollyo chagi Central Lampung hapkido athletes with a percentage increase of 8.4% with a calculated t value > t table, 11.544 > 1.729 which means it is very influential. So it can be concluded that plyometric exercises (jumping lunges and squat jumps can both be used to increase the power of dollyo chagi in Central Lampung hapkido athletes.